Effect of Improving Nurses’ Practices on women’s satisfaction diagnosed with Reproductive Cancer undergoing Chemotherapy - khede, Amal Mousa Mohamed; Attia, Aziza; Farouk, Om-Elsaad; Mostafa, Eman (International Journal of Psychosocial Rehabilitation, 2020)
Background: Reproductive cancer is an important health problem since it leads to mortality and morbidity of women in all over the world. Aim: evaluate effect of improving Nurses’ practices on women’s satisfaction diagnosed with Reproductive Cancer undergoing Chemotherapy. Setting: The study was conducted at Nasser institute hospital (at oncology department outpatient & inpatient department). Study design: a quasi experimental design was utilized. Sample: All nurses (40) who were working in the pre mentioned study setting during the time of the study and convenient sample,80 women with reproductive cancer Tools: Tool 1 self- administered structured questionnaire sheet, Tool 2 observational checklist, and Tool 3 Women’s satisfaction questionnaire sheets. Results: showed statistically significant improvement in nurses’ practical skills related to chemotherapy administration immediately post intervention and after three month follow up phase and increase Women’s satisfaction level toward care provided by nurses, study confirmed statistically a highly significant positive relation between nurses’ practice and Women’s satisfaction post guidelines intervention. Conclusion: nursing guideline had positive effect on nurses’ practices regarding chemotherapy which had direct effect on women’s satisfaction with nursing care they received. Recommendation: Refreshing courses pre-service and in services training programs to enhance nurse’s practical skills at oncology units. Further research is recommended to identify factors that effect on nurse’s knowledge and their practice related to oncology patient receiving chemotherapy.